STUDY OF LANGUAGE STYLES IN PRESIDENT-ELECT JOE BIDEN’S VICTORY SPEECH - Budi Susatyo; Dholiful Hadi (Universitas Muria Kudus, 2022)
This study is a study of the Language Style in a speech on Youtube com with its subtitle, entitled: President-elect Joe Biden stands on stage with his wife Jill, Saturday, Nov. 7, 2020, in Wilmington, Del. Transcript of President-elect Joe Biden’s victory speech Saturday night in Wilmington, Del., as delivered. Provided by the Biden campaign: The Language Style used by Joe Biden are: Repetition, Metaphor, Euphemism, Persuasion, Climax, Anti-tesis, Repetition, Rhetoric, Idiom, Literal Meaning, Persuasive Slogan.Language Style used by Joe Biden could give a positive comprehension, enthusiasm, motivation, understanding for the effectiveness of the audience as well as the listeners and the viewers. This can be understood from his speech that the audience often pay attention in each language style (can be seen on Joe Biden makes a history speech